A Persistent Fog Event Involving Heavy Pollutants in Yancheng Area of Jiangsu Province. (5th June 2018) - Zhu, Yuying; Zhu, Chengying; Zu, Fan; Wang, Hongbin; Yuan, Chengsong; Jiao, Shengming; Zhou, Linyi
Abstract : In the early December 2013, dense fog involving heavy pollutants lasted for 9 days in the Yancheng area. The characteristics, formation, and lasting mechanisms of this persistent fog were analyzed based on observational data at the Sheyang site, reanalysis data, and final analysis data from NCEP/NCAR, combining with the weather background and meteorological and physical variable fields. Results include that (1) the fog process was characterized by long duration, low visibility, and high pollutants concentration, (2) the atmospheric general circulation contributed to the sustainability and development of the heavily polluted fog, (3) deep inversion was the key thermal factor causing the heavily polluted fog, (4) the fog exhibited obvious outbreaks with good visibility weather turned to severe fog several times, and (5) the weak cold air invasion and radiative cooling were the triggering factors to the sudden enhancement of the fog.